2012
DOI: 10.1177/1040638712457352
|View full text |Cite
|
Sign up to set email alerts
|

Lysine at position 222 of the goat prion protein inhibits the binding of monoclonal antibody F99/97.6.1

Abstract: Prion protein (PrP) is encoded by the PRNP gene, which is highly polymorphic in goats, with polymorphisms encoding amino acid substitutions at the protein level. In the current study, the reactivity of monoclonal antibody (mAb) F99/97.6.1 in binding PrP from goats polymorphic at PRNP codon 222 was investigated. Nervous tissue from 30 scrapie-negative goats with 3 different genotypes (222Q/Q, 222Q/K, and 222K/K) was analyzed by Western blot using mAbs P4 and F99/97.6.1. Although PrP was detected in all 30 sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…PRNP polymorphisms might reduce the sensitivity of the assays in goats carrying specific genotypes by reducing antibodybinding epitopes. 18,20 In our samples, however, statistical analysis did not show any association between failure of each test and goat genotypes (data not shown). The reason for this finding remains therefore unknown and might simply depend on low levels of PrP Sc .…”
mentioning
confidence: 56%
“…PRNP polymorphisms might reduce the sensitivity of the assays in goats carrying specific genotypes by reducing antibodybinding epitopes. 18,20 In our samples, however, statistical analysis did not show any association between failure of each test and goat genotypes (data not shown). The reason for this finding remains therefore unknown and might simply depend on low levels of PrP Sc .…”
mentioning
confidence: 56%
“…The results of our study (Figs. 1, 3), and others, 24 clearly demonstrate that the presence of a sequence variant at 222 reduces sensitivity of Western blot detection of PrP C by F99. This difference is also anticipated to be observed when analyzing PrP Sc by Western blot, IHC, or other immunoassays that use F99, and could lead to an increased number of false-negative results.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 study demonstrated decreased detection of PrP C with F99 by Western blot in goats with at least 1 allele encoding K222 and the complete absence of signal in K222 homozygotes. 24 In our study, we assessed the performance of several antibodies for the detection of PrP C by Western blotting and PrP Sc by IHC when the caprine prion protein was expressed as wild type or several allelic variants that are present in the United States. 37 In addition to F99, our study focused primarily on F89, because this antibody was included in the original third-eyelid testing scheme for sheep 25 ; the aa epitope it recognizes includes sites of allelic variation in caprine PRNP that may be associated with delayed incubation of disease or reduced risk of infection, 4,6,8,13,14 and naturally infected goats with this allelic variation have been identified in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we demonstrated, using a Western blot method, a total inhibition by lysine at position 222 on the binding of the monoclonal antibody (mAb) F99/97.6.1 to goat PrP C in healthy goat brain and we proposed the ratio between the signal intensity given by the mAbs F99/97.6.1 and SAF84 (referred to simply as F99/SAF84) to discriminate goats carrying the 222Q/Q, 222Q/K and 222K/K PrP genotypes [ 19 ]. In the present study, we applied the same approach to investigate the contribution of the PrP 222K variant to PrP res formation in natural and experimental scrapie positive goats.…”
mentioning
confidence: 99%